MOOCs to Semantic Web Education - Gonçalves, Vitor (2019)
The web is a largest information repository which makes multimedia contents available. However, their location is no easy task, mainly since their semantics or meaning can only be captured in their context and in accordance to human perspective. In the past years, the W3C (World Wide Web Consortium) and the international scientific community have been carrying out significant efforts with view to improving the localization, retrieval and reuse of information, which may be inaccessible or stored in servers scattered around the deep web or the invisible web. We are talking about the new web generation: the semantic web. Metadata and ontologies, annotation tools, ontologies tools, agent systems, among other technological developments of Computer Sciences and Artificial Intelligence are the key elements for the development of solutions that are gradually lead to changing the web reality. The main purpose is the integration, interchange and semantic understanding of information not only from the viewpoint of humans, but also from the perspective of machines through the change of the current web into a web of semantic data. But, is there any Massive Open Online Course (MOOC) that contributes to forming people capable of understanding and collaborating in this migration process? In this context, we intend to identify a set of MOOCs oriented to the study of the semantic web and, consequently, to determine the contents transmitted in each of the different courses. As such, through an exploratory research, characterized as documentary, we use as main sources of information as articles and publications on the subject to understand the relevance of the Semantic Web in contemporary education, as well as the importance of MOOC as a vehicle for dissemination and sharing of knowledge in this area.